1993
DOI: 10.1901/jaba.1993.26-53
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Simplified Treatment for Stuttering in Children

Abstract: We investigated the effectiveness of a simplified program for the treatment of stuttering in children. The simplified treatment induded awareness training, in which the subjects learned to detect every occurrence of stuttering; training a response incompatible with stuttering, which involved relaxation and regulation of air flow over the larynx when speaking; and social support, which involved parentdelivered prompts and praise of children's use of the techniques in everyday environments. Eight children were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…Stuttering may involve a number of disfluences in the production of speech, including repetitions of word sounds, words, or phrases; prolongation of a word sound; or a hesitation (sometimes called a block) when attempting to speak Wagaman et al, 1993). These disfluencies disrupt the rhythmic quality of speech and may be accompanied by secondary behaviors that give the indication that the individual is struggling to speak.…”
Section: Who Exhibited Tics Habit Reversalmentioning
confidence: 99%
See 3 more Smart Citations
“…Stuttering may involve a number of disfluences in the production of speech, including repetitions of word sounds, words, or phrases; prolongation of a word sound; or a hesitation (sometimes called a block) when attempting to speak Wagaman et al, 1993). These disfluencies disrupt the rhythmic quality of speech and may be accompanied by secondary behaviors that give the indication that the individual is struggling to speak.…”
Section: Who Exhibited Tics Habit Reversalmentioning
confidence: 99%
“…The issue of assessment is particularly pertinent to research evaluating treatments for habits because many of these behaviors often occur covertly, possibly because of a history of social punishment for the behaviors (e.g., Rapp, Miltenberger, Galensky, Roberts, & Ellingson, 1998;Scotti et al, 1994). Although individuals who stutter or exhibit motor and vocal tics typically engage in these behaviors in the presence of the researchers who can then conduct direct observation assessments (e.g., Azrin & Peterson, 1988Finney et al, 1983;Wagaman et al, 1993), individuals who bite their nails, suck their thumbs, pull their hair, and engage in similar habits may refrain from these behaviors in the presence of the researchers (e.g., Rapp, Miltenberger, Galensky, Roberts, & Ellingson, 1998;. Therefore, it is sometimes necessary to utilize assessment procedures other than direct observation or to modify direct observation procedures to capture the occurrence of the behavior.…”
Section: Assessment Of Behaviors Treated With Habit Reversalmentioning
confidence: 99%
See 2 more Smart Citations
“…Although habit reversal has been shown to be effective, implementation of the entire treatment package tends to be time, labor, and financially intensive (e.g., Woods & Miltenberger, 1995). In an attempt to make treatment more efficient and cost effective, researchers have evaluated simplified versions of the habit-reversal procedure and have concluded that an effective, simplified procedure consists of awareness training and the use of a competing response (Finney, Rapoff, Hall, & Christopherson, 1983;Miltenberger, Fuqua, & McKinley, 1985;Sharenow, Fuqua, & Miltenberger, 1989;Wagaman, Miltenberger, & Arndorfer, 1993). In awareness training, the subject learns to discriminate each occurrence of the tic, and in competing response training, the subject learns to engage in an incompatible behavior contingent on the anticipation or occurrence of the tic.…”
mentioning
confidence: 99%